2019
DOI: 10.1111/anae.14577
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative microcirculatory perfusion and endothelial glycocalyx shedding following cardiac surgery with cardiopulmonary bypass

Abstract: Summary We investigated microcirculatory perfusion disturbances following cardiopulmonary bypass in the early postoperative period and whether the course of these disturbances mirrored restoration of endothelial glycocalyx integrity. We performed sublingual sidestream dark field imaging of the microcirculation during the first three postoperative days in patients who had undergone on‐pump coronary artery bypass graft surgery. We calculated the perfused vessel density, proportion of perfused vessels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 40 publications
6
111
0
Order By: Relevance
“…In both studies, median PBR values remained unchanged while an improvement in microvascular parameters was seen in the treatment groups. In contrast, two longitudinal studies conducted in patients undergoing cardiac surgery suggested the existence of an association between the alterations in microcirculation parameters and eGC dimensions [18,41]: Koning et al assessed the sublingual microcirculation and eGC dimensions perioperatively in 36 patients undergoing cardiac surgery with or without cardiopulmonary bypass (CPB) [18]. The CPB procedure increased the PBR and decreased the PVD, whereas offpump surgery decreased the PBR without affecting the PVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, median PBR values remained unchanged while an improvement in microvascular parameters was seen in the treatment groups. In contrast, two longitudinal studies conducted in patients undergoing cardiac surgery suggested the existence of an association between the alterations in microcirculation parameters and eGC dimensions [18,41]: Koning et al assessed the sublingual microcirculation and eGC dimensions perioperatively in 36 patients undergoing cardiac surgery with or without cardiopulmonary bypass (CPB) [18]. The CPB procedure increased the PBR and decreased the PVD, whereas offpump surgery decreased the PBR without affecting the PVD.…”
Section: Discussionmentioning
confidence: 99%
“…The CPB procedure increased the PBR and decreased the PVD, whereas offpump surgery decreased the PBR without affecting the PVD. Dekker et al analyzed the sublingual microvasculature in 17 patients undergoing non-pulsatile CPB [41]. They found a small increase in PBR and a sustained decrease in PVD and PPV during the 72-h follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of glycocalyx dimensions in the phosphorylcholine coating group after cardiac surgery is most likely the result of step-by-step shedding of its constituents, which is in accordance with previous studies. 5,7,20 The endothelial glycocalyx consists of core proteoglycans, such as syndecans, that are firmly bound to the endothelial cell membrane. These proteoglycans are the backbone for binding glycosaminoglycan side chains, such as the negatively charged glycosaminoglycan heparan sulphate, that influences the interaction of chemokines with endothelial receptors and is distributed predominately on the luminal side of the glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous NO was prone to be depleted by extracorporeal circulation in cardiac surgery, which may impair microcirculation and cause tissue ischemia, metabolic abnormalities, and organ dysfunction . In our study, intravenous administration of high‐dose NTG provided exogenous NO, which may normalize the physiologic regulation of microvascular networks during CPB.…”
Section: Discussionmentioning
confidence: 71%
“…CPB in cardiac surgery carries the risk of end‐organ damage, exerting a significant impact on outcomes in cardiac surgical patients . CPB‐related microcirculatory derangement contributes to the pathogenesis of organ damage, including tissue hypoperfusion, ischemia‐reperfusion, oxidative stress response, and hemolysis . Hemolysis elevates concentration of plasma free hemoglobin, which may scavenge and deplete intravascular NO …”
Section: Introductionmentioning
confidence: 99%